Convulsant action of D,L-homocysteic acid and its stereoisomers in immature rats - Mares, P; Folbergrová, J; Langmeier, M; Haugvicová, R; Kubová, H (Epilepsia, 1997)
PURPOSE: We wished to characterize the convulsant effect of homocysteic acid (HCA) in developing rats. METHODS: Seizures were induced in 7-, 12-, 18-, and 25-day-old rats by intraperitoneal (i.p.) administration of D,L-HCA and in 12-day-old rats by i.p. injection of L- and D-stereoisomers of HCA. The animals were observed for 30 min after injection. The incidence, latencies, pattern of motor seizures, and all behavioral phenomena were noted. Fifty percent convulsant dose (CD50) values were calculated by probit analysis. Electrocorticograms (ECoG) were recorded after injection. RESULTS: HCA did not elicit minimal clonic seizures whereas generalized tonic-clonic seizures (GTCS) occurred in all the age groups studied. Flexion (emprosthotonic) convulsions occurred to postnatal day 18. ECoG recordings exhibited delta activity in younger pups and sharp graphoelements in older pups, but electroclinical correlation was poor. Young animals were more sensitive to the convulsant effect of D,L-HCA. In addition, D-HCA was significantly more effective than L-HCA in inducing both flexion and generalized seizures. CONCLUSIONS: Our data clearly indicate that seizures induced by HCA differ from those evoked by homocysteine. There are no qualitative differences in the motor pattern of seizures induced by the two stereoisomers of HCA, but marked differences were apparent in the very first signs of their action. These differences might be due to interaction with different glutamate receptor subtypes.
Keywords: Animals; novorozená zvířata; injekce intraperitoneální; vztah mezi dávkou a účinkem léčiva; glutamátové receptory; Convulsants; hipokampus; Seizures; Electroencephalography; Injections, Intraperitoneal; Animals, Newborn; chování zvířat; neurony; Stereoisomerism; stereoizomerie; Receptors, Glutamate; homocystein; Neurons; Dose-Response Relationship, Drug; konvulziva; krysa rodu Rattus; Behavior, Animal; Hippocampus; Homocysteine; zvířata; elektroencefalografie; Rats; záchvaty